Sheathed Molecular Junctions for Unambiguous Determination of Charge‐Transport Properties - Lucia Herrer; Saman Naghibi; Ivan Marín; Jonathan S. Ward; Jose María Bonastre; S. J. Higgins; Santiago Martín; Andrea Vezzoli; Richard John Nichols; José Luis Serrano; Pilar Cea (Advanced Materials Interfaces, 2023)
Abstract Future applications of single‐molecular and large‐surface area molecular devices require a thorough understanding and control of molecular junctions, interfacial phenomena, and intermolecular interactions. In this contribution the concept of single‐molecule junction and host‐guest complexation to sheath a benchmark molecular wire–namely 4,4′‐(1,4‐phenylenebis(ethyne‐2,1‐diyl))dianiline – with an insulating cage, pillar[5]arene 1,4‐diethoxy‐2‐ethyl‐5‐methylbenzene is presented. The insertion of one guest molecular wire into one host pillar[5]arene is probed by 1H‐NMR (nuclear magnetic resonance), whilst the self‐assembly capabilities of the amine‐terminated molecular wire remain intact after complexation as demonstrated by XPS (X‐ray photoelectron spectroscopy) and AFM (atomic force microscopy). Encapsulation of the molecular wire prevents the formation of π‐ π stacked dimers and permits the determination of the true single molecule conductance with increased accuracy and confidence, as demonstrated here by using the STM–BJ technique (scanning tunneling microscopy– break junction). This strategy opens new avenues in the control of single‐molecule properties and demonstrates the pillararenes capabilities for the future construction of arrays of encapsulated single‐molecule functional units in large‐surface area devices.